Ordinary Muon Capture for Double Beta Decay and Anti-Neutrino Nuclear Responses - Hashim, Izyan Hazwani; Ejiri, Hiroyasu (Frontiers in Astronomy and Space Sciences, 2021)
This is a brief review on ordinary muon capture (OMC) experiments at Research Center for Nuclear Physics (RCNP) Osaka University to study neutrino nuclear responses for double beta decays (DBDs) and astro anti-neutrinos. OMC usually leaves the nucleus in a highly excited unbound state. OMC is a charge exchange reaction via the charged weak boson as given by(μ, νμ) reactions with μ and νμ being the muon and muon neutrino. Subjects discussed include (i) unique features of μ-CER for studying neutrino nuclear responses for DBDs and astro anti-neutrinos, (ii) experiments of μ-CERs on 100Mo and natMo to study neutrino nuclear responses for DBDs and astro anti-neutrinos, (iii) impact of the μ-CER results on neutrino nuclear responses for DBDs and astro anti-neutrinos. Remarks and perspectives on μ-CER experiments for neutrino nuclear responses are briefly described.